Implementasi Proyek Magic Paper Dalam Pembelajaran IPS Untuk Meningkatkan Kesadaran Lingkungan Peserta Didik SMP - Soekma Cempaka; Nurrahma, Sofia; Siti Logayah, Dina (STKIP Al-Amin Dompu, 2025)
The Magic Paper project is an environmental innovation that combines recycled waste paper with the planting of plant seeds, resulting in plantable paper. This article discusses the implementation and socialization of the Magic Paper project in social studies learning in junior high schools to increase students' awareness and environmentally friendly behavior. The method used is a descriptive qualitative method and analysis of the implementation of the Magic Paper project in the classroom in social studies lessons. Data collection was carried out through observation, interviews, and documentation of learning activities. The results of the study indicate that the implementation of the Magic Paper project in social studies learning can increase students' environmental awareness through meaningful and contextual learning experiences. This project integrates the concepts of Reduce, Reuse, and Recycle (3R) with the social studies material on the Role of Social Institutions in the Utilization of Natural Resources. Students not only understand the theoretical concept of environmental conservation, but are also directly involved in the real practice of paper recycling.